Downregulation of Autophagy-Related Proteins 1, 5, and 16 in Testicular Germ Cell Tumors Parallels Lowered LC3B and Elevated p62 Levels, Suggesting Reduced Basal Autophagy - Liu, He; He, Zhaoyue; Bode, Peter; Moch, Holger; Simon, Hans-Uwe (Frontiers in Oncology, 2018)
Autophagy is a cellular “self-digestion” process known to be essential for various physiological and pathological pathways, including cancer, where its role appears to be context-dependent. In this work, we aimed to investigate the level of autophagy by evaluating the expression of key autophagy-related proteins (ATGs) in testicular germ cell tumors (TGCT) for which autophagy has been rarely investigated. We decided to use an immunohistochemical (IHC) staining approach employing a tissue microarray (TMA). Software-based evaluation of the integrated optical densities (IODs) of these proteins indicated a significant downregulation of ATG1, ATG5 and ATG16L1. Accordingly, reduced levels of microtubule-associated proteins 1A/1B light chain 3B (LC3B) were found to parallel increases in sequestosome-1 (SQSTM1 or p62), a protein normally degraded via autophagy, suggesting an in vivo reduction in autophagy with TGCT. Thus, our work provides evidence for a tumor suppressive function of autophagy in the development of TGCT and supports the concept of a context-dependent role of autophagy in tumorigenesis which is tumor type-dependent.